A qualitative study of primary teachers' classroom feedback rationales. Issue 2 (3rd April 2018) - Eriksson, Elisabeth; Boistrup, Lisa Björklund; Thornberg, Robert
Abstract: Background: As part of teachers' everyday classroom assessment practice, feedback can be seen as connected to the formative function of assessment, with the aim of helping students in their learning processes. Much research on teacher feedback focuses precisely on the feedback's formative quality. However, in order to strengthen our understanding about the nature of teacher feedback, we also need to understand more about teachers' rationales for giving feedback to their students, especially in primary school settings. Purpose: The present study aimed to explore and conceptualise primary school teachers' rationales for giving students feedback. Sample: Thirteen Swedish primary school teachers ( 10 women and 3 men) with 4 to 40 years of teaching experience working with students aged 7–9 years-old (grades 1–3), participated in the study. An open sampling procedure was adopted to recruit the teachers. Design and methods: Data were collected using a semi-structured interview approach. We employed a constructivist grounded theory design for the coding and analysis of the transcribed data. Results: Analysis indicated that two main concerns emerged as regulating teachers' assessment practices. These addressed what the teachers perceived as (1) students' academic needs and (2) students' behavioural and emotional needs. According to the findings, the teachers' rationales for giving students feedback were based on those needs, and dependent on factors such as situation, relationships, time and effort. This resulted in a constant comparison and weighing of different needs by the teachers. Some needs were described as prioritised before others, which caused some rationales to be identified as taking precedence over others. Discussion and conclusions: Based on a systematic analysis of – and thus grounded in – interview data from primary teachers, the current qualitative study offers a framework for surveying, understanding and discussing teacher feedback. Overall, the study showed how everyday practices of classroom assessment and classroom management overlapped, thus underlining the importance in teacher education of understanding classroom assessment, classroom management and the relationships between the two.